PERJALANAN IJTIHAD DALAM PERKEMBANGAN FIKIH - FATHURRAHMAN AZHARI (Syariah: Jurnal Hukum dan Pemikiran, 2014)
The growth and development of fiqh has a close relationship with ijtihad. Results of ijtihad by mujtahid have contribution in the establishment and development of fiqh. In other words, the growth and development of fiqh is depend on how much mujtahid use the ability and knowledge to make a legal product. Declining in the development of fiqh is caused by weakness of the Ulema to perform ijtihad. After the golden age of Islam, Ulema has no longer perform ijtihad as was done by the his predecessors. Moreover, the Ulema made a statement that ijtihad was closed, so the development of fiqh has decreased. To restore the spirit of ijtihad, the Ulema now have to perform various concepts of ijtihad.